2015
DOI: 10.1142/s0217984915502267
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the experimental thermal cleaning procedure in LiF:Mg,Ti and investigation of the origin of the first-order kinetics of its peaks

Abstract: In this paper, the simulation of the thermal cleaning procedure in LiF:Mg,[Formula: see text]Ti as well as the investigation of the origin of its glow-peaks have been performed by six electron trapping levels and one recombination center phenomenological model. The most generally accepted parameter of the glow-peaks 1 to 5 of LiF:Mg,[Formula: see text]Ti is their first-order kinetics; this was particularly investigated by the use of the random variation of the kinetic parameters method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…2 for 140°C (it has to be noted that only first temperature is shown). The calculated kinetic parameters for each of the three peaks are shown in Table 1 and the values are comparable to the Refs [10,11]. The frequency factor was evaluated using the following equation:…”
Section: Fig1 Thermal Treatment For Different Heating Temperaturesmentioning
confidence: 67%
See 2 more Smart Citations
“…2 for 140°C (it has to be noted that only first temperature is shown). The calculated kinetic parameters for each of the three peaks are shown in Table 1 and the values are comparable to the Refs [10,11]. The frequency factor was evaluated using the following equation:…”
Section: Fig1 Thermal Treatment For Different Heating Temperaturesmentioning
confidence: 67%
“…The fading of the thermoluminescent (TL) output signal is a seriously annoying property of thermoluminescent dosimeters (TLDs) that is important to characterize, in order to accurately relate TL output with amount of radiation exposure [1,[14][15]. Previous authors used postirradiation treatments to empty the low temperature TL traps and remove the low temperature glow peaks before readout to reduce or eliminate this fading [5,10,[16][17]. Izak-Biran et al [5] concluded that the application of post-irradiation procedure significantly reduces fading due to the removal of the minimum temperature peaks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LiF:Mg,Ti is largely employed to study the TL effects of parameters such as supralinearity, impurity concentration, radiation damage, etc. [1, 5,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…According to this terminology, kinetic parameters, such as the activation energy E, frequency factor s, and kinetic order b, for the so-called glow peak 5 of LiF:Mg,Ti have been a major topic of TL research for many years. The interest on this topic is not only limited to the fact that LiF:Mg,Ti has been extensively used as a basic TL dosimeter, but rather enhanced due to specific peculiarities related with the reported values of E, s and b as well [6,7,24].…”
Section: Introductionmentioning
confidence: 99%